Толерантность к неопределенности как способ увеличения уровня адаптивности к профессиональной деятельности - Квасник, Ольга Витальевна (Institutul Internațional de Management Imi-Nova, 2018)
The article considers the scientific interpretation of the concept of tolerance for uncertainty in the context of professional activity. The main characteristics of the components of the structure of tolerance for uncertainty are identified, its place in the structure of the personality of a professional is determined. A list of techniques that contribute to the formation or development of the concept under study is given.

У статті розглядається наукова інтерпретація поняття толерантності до невизначеності в контексті професійної діяльності. Основні характеристики компонентів структури толерантності до виявленої невизначенності, визначено її місце в структурі особистості професіонала. Наведено прийоми, які сприяють формуванню чи розвитку досліджуваного поняття.
Keywords: толерантность; личность; профессионалы; толерантность к неопределенности; адаптивность; профессиональная деятельность; игровой метод; тренинг